Sepsis affects kidney graft function and one-year mortality of the recipients in contrast with systemic inflammatory response - Protus, Marek; Uchytilova, Eva; Indrova, Veronika; Lelito, Jan; Viklicky, Ondrej; Hruba, Petra; Kieslichova, Eva (Frontiers in Medicine, 2022)
Background: Infections remain a major cause of morbidity and mortality after kidney transplantation, and if sepsis occurs, acute kidney graft injury can develop. The aim of our study was to determine the effect of sepsis on kidney graft function and recipient’s mortality. Methods: A prospective, observational, single center study was performed. Selected clinical and biochemical parameters were recorded and compared between the experimental (with sepsis, n=34) and control group (with systemic inflammatory response syndrome, n=31) of kidney allograft recipients. Results: Sepsis worsened both patient‘s (HR=14.8, p=0.007) and graft survival (HR=15.1, p=0.007). Overall one-year mortality was associated with age, (HR=1.08, p=0.048), APACHE II score (HR=1.13, p=0.035), and immunosuppression combination (HR=0.1, p=0.006), graft survival with APACHE II (HR=1.25, p=0.004) and immunosuppression. In septic patients, mortality correlated with maximal dose of noradrenalin (HR=100. 9, p=0.008), fungal infection (HR=5.64, p= 0.024), SAPS II score (HR=1.1, p=0.033) and mechanical ventilation (HR=5.9, p= 0.033), graft survival was influenced by renal replacement therapy (HR=21.2, p= 0.005), APACHE II (HR=1.19, p= 0.035), and duration of mechanical ventilation (HR=1.01, p= 0.015). Conclusion: In contrast with systemic inflammatory response, septic kidney allograft injury is associated with early graft loss and may represent a significant risk of mortality.